Prevalence of HPV/p16+ infection among oropharyngeal squamous cell carcinoma patients in a tertiary care centre in Southern India - V. Jawahar; S. Banerjee; J. Kini; S. Sreeram; M. S. Athiyamaan; J. Sunny; A. Krishna; C. Srinivas; D. Lobo; B. S. Mokkapatti (Успехи молекулярной онкологии)
Introduction. Oropharyngeal squamous cell carcinomas are often found to be associated with human papilloma virus (HPV) infection. The prevalence of HPV infection among oropharyngeal squamous cell carcinomas patients in India is comparatively lower to that of the same worldwide. Aim. To find out the prevalence of HPV infection among oropharyngeal squamous cell carcinomas patients who presented in our hospital.Settings and design. Retrospective cross-sectional study.Materials and methods. Tissue block of 60 patients with biopsy-proven oropharyngeal squamous cell carcinomas were subjected to immunohistochemistry for evaluating p16 expression. The p16 expression pattern was correlated with the demographic details. Data was entered in Microsoft Excel and Statistical Analysis was done with the help of SPSS version 22 (IBM Corp. Released, 2013. IBM SPSS Statistics for Windows, Version 22.0. Armonk, NY: IBM Corp.).Results. Prevalence of HPV infection in our study was found to be 11.7 %. 85.8 % of all p16-positive patients had moderate-well differentiated disease. 6 out of 7 p16-positive patients had higher T stage (T3–4). All the patients who were p16+ were found to have a higher Nodal stage (N2–3). 100 % of all p16+ patients were found to have stage IV disease.Conclusion. Prevalence of HPV infection was found to be similar to that of previous studies conducted in India. These patients also presented with advanced nodal disease at presentation and thereby, an advanced overall stage.